Sale, Purchase, And Accounting Information System Using Analytic Hierarchy Process For Supplier Selection In Store X - Effendi, Aldi; Imbar, Radiant Victor (Teknik dan Ilmu Komputer, 2017)
AbstractÃÂ Nowadays information technology is very important to help human decide. Company X is a store selling building tools, such as cement, toilet, and irons. Company X is looking for the best supplier to gain the highest profit margin. Meanwhile, the company does not have accounting report that records each transaction. As a result, the owner didnÃ¢â¬â¢t know the profit gained or loss suffered in a certain period. This application hopefully could help the store owner make daily sales process effective and eficient. DSS (Decision Support System) with AHP (Analytical Hierarchy Process) method is used to solve the decision making problems with the suppliers. With the help of DSS, the store owner could easily choose the best supplier. From the test conducted, it is proven that 30 purchases made using this application, the profit gained is increasing, and the return rate is declining. AHP is used to analyze the data given to the application, calculate it, and rank the processed data. The integrated accounting report in the application could help the owner know the profit or loss during certain periods. The accounting report consists of journal, ledger, balance sheet, and income statement.ÃÂ Keywords: Decision Support System, Analytical Hierarchy Process, Accounting